The lamps of late antiquity from Rhodes : 3rd-7th centuries AD - Katsioti, Angeliki (Archaeopress Publishing Ltd, 2017)
This study focuses on the recording, study and publication of the corpus of the Late Antique lamps dating from the 3rd to the 7th centuries as found in rescue excavations in the town of Rhodes. The aim here is to present the diachronic changes in the artistic sensibility and preferences of this particular market.